Activation in vitro of RNA polymerase II and III directed transcription by baculovirus produced E1A protein. - Patel, G (1990)
The baculovirus expression system has been successfully used to overproduce a number of different protein products. In this report we describe the construction of a recombinant baculovirus containing the adenovirus E1A 13s cDNA sequence. Infection of insect cells with this virus results in the production of phosphorylated E1A protein. The phosphorylation pattern appears to be similar to the complex pattern associated with E1A protein synthesis in mammalian cells. Purified baculovirus generated E1A protein activated transcription of specific poIIII promoters both in microinjected Xenopus laevis oocytes and in HeLa cell in vitro transcription extracts. The protein also stimulates in vitro transcription of the poIIII transcribed VA1 gene.